2014
DOI: 10.4238/2014.december.12.19
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia induces dysregulation of local renin-angiotensin system in mouse Lewis lung carcinoma cells

Abstract: ABSTRACT. The renin-angiotensin system (RAS) influences cancer biology and is frequently dysregulated in malignancy. However, regulation of tumor local RAS remains poorly understood. Hypoxia is a hallmark of solid tumors and affects nearly every major aspect of cancer biology. Previous studies have shown that hypoxia can regulate RAS expression in somatic tissues and cells. The aim of this study was to investigate the influence of hypoxia on local RAS expression in mouse Lewis lung carcinoma (LLC) cells. For h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…Current evidence supports the idea that both host and tumor RAS are important for tumor growth and angiogenesis in cancer (10,15). As a new part of RAS, the ACE2/Ang-(1-7)/Mas axis also plays an important role in cancer (16,17). Recent studies have shown that low ACE2 expression may be a useful indicator of poor prognosis in HCC and gallbladder cancer (18,19).…”
Section: Discussionmentioning
confidence: 62%
“…Current evidence supports the idea that both host and tumor RAS are important for tumor growth and angiogenesis in cancer (10,15). As a new part of RAS, the ACE2/Ang-(1-7)/Mas axis also plays an important role in cancer (16,17). Recent studies have shown that low ACE2 expression may be a useful indicator of poor prognosis in HCC and gallbladder cancer (18,19).…”
Section: Discussionmentioning
confidence: 62%
“…Most intriguingly, this regulation is diphasic: in the early phase, after 6 h hypoxia, AT1R protein is decreased, whilst AT2R protein is increased; yet if hypoxia is continued up to 24 h this effect is reversed, with AT1R protein significantly increased and AT2R decreased (Fan et al . ). Employing specific pharmacological inhibitors, Fan et al .…”
Section: Discussionmentioning
confidence: 97%
“…Employing specific pharmacological inhibitors, Fan et al . () concluded that this diphasic response may be due to a bi‐directional control mechanism: hypoxia enhances the expression of AT1R and AT2R via increased Ang II, but elevated AT2R inhibits AT1R during the early stage whilst AT1R inhibits AT2R expression as hypoxia continues. This may explain why neither the AT1R nor the AT2R were significantly altered in our hypoxia–reperfusion model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RAS was demonstrated to be involved in tumor occurrence and development (4648). For example, AngII was able to promote epithelial-to-mesenchymal transition in intrahepatic cholangiocarcinoma (38), and angiotensin-converting enzyme inhibitor suppresses growth of colorectal cancer cells (49).…”
Section: Discussionmentioning
confidence: 99%